Structural remodeling of SARS-CoV-2 spike protein glycans reveals the regulatory roles in receptor-binding affinity. (12th November 2022) - Hsu, Yen-Pang; Frank, Martin; Mukherjee, Debopreeti; Shchurik, Vladimir; Makarov, Alexey; Mann, Benjamin F
Abstract: Glycans of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein are speculated to play functional roles in the infection processes as they extensively cover the protein surface and are highly conserved across the variants. The spike protein has been the principal target for vaccine and therapeutic development while the exact effects of its glycosylation remain elusive. Analytical reports have described the glycan heterogeneity of the spike protein. Subsequent molecular simulation studies provided a knowledge basis of the glycan functions. However, experimental data on the role of discrete glycoforms on the spike protein pathobiology remains scarce. Building an understanding of their roles in SARS-CoV-2 is important as we continue to develop effective medicines and vaccines to combat the disease. Herein, we used designed combinations of glycoengineering enzymes to simplify and control the glycosylation profile of the spike protein receptor-binding domain (RBD). Measurements of the receptor-binding affinity revealed opposite regulatory effects of the RBD glycans with and without sialylation, which presents a potential strategy for modulating the spike protein behaviors through glycoengineering. Moreover, we found that the reported anti-SARS-CoV-(2) antibody, S309, neutralizes the impact of different RBD glycoforms on the receptor-binding affinity. In combination with molecular dynamics simulation, this work reports the regulatory roles that glycosylation plays in the interaction between the viral spike protein and host receptor, providing new insights into the nature of SARS-CoV-2. Beyond this study, enzymatic glycan remodeling offers the opportunity to understand the fundamental role of specific glycoforms on glycoconjugates across molecular biology.